Pelayanan dan Keuangan: Suatu Upaya Meningkatkan Keuangan Gereja dalam Mendukung Pemberitaan Kabar Baik di Calon Resort GKE Bulik Timur (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Many churches face significant challenges in effectively carrying out their Gospel mission amidst limited resources, and one such challenge is the Kalimantan Evangelical Church (GKE), particularly in the Calon Resort (Cares) of GKE Bulik Timur. The author used a qualitative approach to examine the natural conditions of the object. The researcher served as the key instrument, and purposive sampling was used. The results of this study are: Limited funds due to the spiritual health of congregation members hinders ministry, particularly in PKB mission activities and congregational development; Low financial support from congregation members for improving church services is caused by: weak theological understanding and limited income; The church's efforts and strategies to improve finances theologically and responsibly include: instilling a sense of giving through sermons, spiritual development, and investing in oil palm plantations. Oil palm plantations in several congregations in Cares GKE Bulik Timur have become a solution to financial constraints, ensuring adequate funding for services.